2008
DOI: 10.1002/gps.2099
|View full text |Cite
|
Sign up to set email alerts
|

The association of individual and facility characteristics with psychiatric hospitalization among nursing home residents

Abstract: Both resident and facility characteristics impact risk for psychiatric hospitalization. Attention to identified predictors may reduce risk and improve outcomes for nursing home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…Conversely, we found that older residents with Alzheimer’s disease or other dementias had a lower likelihood of hospitalization. This finding differed from another study that found dementia increased the risk of hospitalization for nursing home residents (Becker et al., 2009). One explanation is that residents with Alzheimer’s disease or dementia may be more closely supervised by assisted living facility staff members.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Conversely, we found that older residents with Alzheimer’s disease or other dementias had a lower likelihood of hospitalization. This finding differed from another study that found dementia increased the risk of hospitalization for nursing home residents (Becker et al., 2009). One explanation is that residents with Alzheimer’s disease or dementia may be more closely supervised by assisted living facility staff members.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, CHF was a risk factor for a majority of avoidable hospitalizations among nursing home residents (Spector, Limcangco, Williams, Rhodes, & Hurd, 2013). In contrast, dementia was associated with a lower likelihood of hospitalization (Becker, Andel, Boaz, & Howell, 2009). Also, nursing home resident age was positively associated with hospitalizations (Carter, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lower health care costs for those living with dementia were driven by lower hospital admissions, emergency presentations, medical services, and pharmaceutical use. This has been observed previously in people with dementia in long‐term care and in the last few years of life . These differences may be a function of the baseline differences between the groups; comorbidities were marginally lower and functional status was worse for those with dementia.…”
Section: Discussionsupporting
confidence: 73%
“…However, psychiatric problems that could be addressed or avoided with timely mental health services all too often worsen until hospitalization is required. Other studies suggest psychiatric hospitalizations expose residents to multiple health risks such as delirium, relocation stress syndrome, and increased mortality (Becker et al, 2009; Mallick & Whipple, 2000; Ouslander, Weinberg, & Phillips, 2000). …”
Section: Outcome-based/composite Quality Measuresmentioning
confidence: 99%
“…For example, in analyses of MDS assessments from a subset of states, two separate studies failed to obtain a statistically meaningful difference in the treatment of depression across ownership types (Lapane & Hughes, 2004; Levin et al, 2007). Similarly, a study of Florida nursing homes showed no significant difference in psychiatric hospitalizations by ownership (Becker et al, 2009), and analyses of the 1987 National Medical Expenditure Survey suggested no significant difference in specialist mental health services use across nonprofit and for-profit nursing homes. Using a range of structure, process and outcome measures of quality, Castle and Shea (1998) also found little consistent evidence that for-profit nursing homes provided poorer quality of care to residents with mental illness.…”
Section: Predictors Of Quality Carementioning
confidence: 99%